KEMAMPUAN RESIN DALAM MENURUNKAN KADAR KALSIUM & MAGNESIUM PADA AIR LAUT DI PELABUHAN MUARA ANGKE JAKARTA UTARA - Agit Renaldy (FT-USNI, 2019)
One process of seawater in order to reduce the level of hardness of calcium and mangnesium in seawater is done by draining the water into a column containing M-500 monoplus cation resin (IR-120). This trial aims to determine the effectiveness of calcium and magnesium uptake compared with time variation (t), control, 15 minutes, 30 minutes and 60 minutes. Ca content of time variation (t) ie, for control treatment of Ca content was obtained at 565 mg / l, treatment time for 15 minutes was obtained 355 mg / l, for treatment time of 30 minutes was obtained at 350 mg / l and for treatment time filtration for 60 minutes was obtained at 176 mg / l. mg content was obtained at 123 mg / l, treatment time of 15 minutes was obtained 114 mg / l, for treatment time of 30 minutes was obtained at 99 mg / l and for treatment of 60 minutes was obtained at 71 mg / l.